2013
DOI: 10.1097/bsd.0b013e318286fc18
|View full text |Cite
|
Sign up to set email alerts
|

Posterior-approach Vertebral Replacement With Rectangular Parallelepiped Cages (PAVREC) for the Treatment of Osteoporotic Vertebral Collapse With Neurological Deficits

Abstract: PAVREC provided a satisfactory clinical and radiologic outcome without severe complications. This procedure can be a treatment option for osteoporotic vertebral collapse and an alternative to an anterior-approach or single posterior-approach reconstruction with a cylindrical cage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…March L et al reported that on the osteoporotic vertebral body, the peripheral regions of the endplate have greater resistance to subsidence, whereas the central region provides the least resistance9). So grafted autobone inside and around the wide cages (more than 22mm) is likely to be advantage for bony union due to adequate stress transmission and proper blood flow16). Although, grafted autobone itself is already changed weakly, which can help prevent to some degrees of cage subsidence16).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…March L et al reported that on the osteoporotic vertebral body, the peripheral regions of the endplate have greater resistance to subsidence, whereas the central region provides the least resistance9). So grafted autobone inside and around the wide cages (more than 22mm) is likely to be advantage for bony union due to adequate stress transmission and proper blood flow16). Although, grafted autobone itself is already changed weakly, which can help prevent to some degrees of cage subsidence16).…”
Section: Discussionmentioning
confidence: 99%
“…So grafted autobone inside and around the wide cages (more than 22mm) is likely to be advantage for bony union due to adequate stress transmission and proper blood flow16). Although, grafted autobone itself is already changed weakly, which can help prevent to some degrees of cage subsidence16). There are some possible causes for the formation of a pseudoarthrosis4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If the fractured vertebra was severely collapsed and showed decreased intravertebral instability, the vertebrae were partially or totally resected using a posterior approach and replaced with large, rectangular, parallelepiped cages and autograft bone and pedicle screwing was then applied 1–3 levels above and below the lesion, considering the affected vertebral level and osteoporosis severity [ 9 ]. This technique was termed “posterior approach vertebral replacement with rectangular parallelepiped cage” (PAVREC) [ 9 ]. The details of the PAVREC procedure have been described elsewhere [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, in some patients with severely collapsed vertebrae, the vertebrae were partially resected and replaced with large, rectangular, parallelepiped cages (REC cages) and autograft bone. This technique is a modification of the PLIF technique and was termed Bposterior-approach vertebral replacement with REC cages( PAVREC) [15]. PAVREC was applied as a part of spinal correction combined with multilevel PLIF.…”
Section: Corrective Spinal Surgerymentioning
confidence: 99%